Pengaruh Penambahan TiO₂ terhadap Kemampuan Distribusi Warna Cetakan pada Kertas Komposit Berbasis Ampas Tebu - Fitri Kusuma Dewi; Emmidia Djonaedi; Rachmah Nanda Kartika (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
The processing of natural fibers as raw materials for paper has grown over the past few years. However, the use of composite paper as a printing substrate has several drawbacks. One of them is the low color reproduction quality of printed images on paper made from natural fibers, caused by the insufficient whiteness of the paper. This study aims to investigate the effect of titanium dioxide (TiO₂) addition on the color reproduction quality of composite paper based on sugarcane bagasse fiber. TiO₂ was varied at concentrations of 0%, 10%, and 20%. Printing process was carried out using an inkjet printer with standard CMYK and RGB color patches. After that, the printed results were measured using colorimeter with D65 illuminant. Color distribution analysis was processed using MATLAB software. The results showed that the addition of TiO₂ increased the whiteness of the paper, as indicated by the higher L* values. The color gamut visualization demonstrated that the gamut area expanded as the TiO₂ content increased. This result shows that the addition of TiO₂ affects the color reproduction quality of composite paper.